Open, prospective, Multi-Center, Two-Part study of patient preference with monthly ibandronate therapy in women with postmenopausal osteoporosis switched from daily or weekly alendronate or risendronate-BONCURE: Results of Turkish sub-study - (:unkn) unknown (My University, 2012)
Amaç: BONCURE (Mevcut Bisfosfonat Kullanıcıları İçin Bonviva Bölgesel Avrupa Çalışması) ile daha önce günlük veya haftalık alendronat veya risendronat alan postmenopozal osteoporozu olan kadınlarda aylık ibandronat için hasta tercihinin değerlendirilmesi amaçlandı. Gereç ve Yöntemler: Bu prospektif, açık-etiketli çalışma, iki ardışık aşamadan oluşmuştur: A (tarama) ve B (tedavi) aşaması. A aşamasına kaydolan hastalar Aday Kimlik Anketi (CIQ) tamamladı. B aşamasında, Osteoporoz Hasta Memnuniyeti Anketi (OPSAT Q) tamamladıktan sonra, hastalar 6 ay boyunca aylık oral 150 mg ibandronat aldı. Tedaviden sonra, hastalar OPSAT-Q ve Tercihi Anketi tamamladı. Bulgular: Türkiye’den 223 hasta (yaş ortalaması 63,7±9,51) A aşamasına dahil edildi. Bunların arasında, 103’ü (%46,2) en az bir CIQ sorusunu "EVET" yanıtladı. Ortalama bileşik OPSAT-Q alan puanları; kolaylık (ortalama değişiklik, 15,3±17,7 puan), yaşam kalitesi (10,4±20,4 puan), genel memnuniyet (11,9±22,7 puan) ve yan etkiler (3,3±18,8 puan) için arttı. Altıncı ayda 177 hasta (%92,7) bir kez aylık doz programını tercih etti ve %99,0’u çalışma tedavisi ile uyumlu (≥%80) idi. Otuz hasta (%15,6) çoğunlukla gastrointestinal olan hafif ve orta şiddette advers olay yaşadı. Sonuç: Postmenopozal osteoporozu olan kadınlar, günlük veya haftalık bifosfonat tedavisine göre aylık ibandronatı daha çok tercih etmekte ve bu tedavi ile daha memnun ve uyumlu olmaktadır. (Türk Os te opo roz Dergisi 2012;18:1-7)

Aim: BONCURE (Bonviva for Current Bisphosphonate Users Regional European Trial), aimed to evaluate patient preference with monthly ibandronate in women with postmenopausal osteoporosis who previously received daily or weekly alendronate or risendronate. Materials and Methods: This prospective, open-label study consisted of two sequential stages, Part A (screening) and Part B (treatment). Patients enrolled into Part A completed the Candidate Identification Questionnaire (CIQ). In Part B, after completing the Osteoporosis Patient Satisfaction Questionnaire (OPSATQ), patients received monthly oral ibandronate 150 mg for 6 months. Following treatment, patients completed the OPSAT-Q and Preference Questionnaire. Results: A total of 223 patients (mean age, 63.7±9.51 years) were enrolled in Part A from Turkey. Among them, 103 (46.2%) answered “YES” to at least one CIQ question. The mean composite OPSAT-Q domain scores increased for convenience (mean change, 15.3±17.7 points), quality of life (10.4±20.4 points), overall satisfaction (11.9±22.7 points), and side effects (3.3±18.8 points). At month 6, 177 subjects (92.7%) preferred once-monthly dosing schedule and 99.0% were compliant (≥80%) with study treatment. Thirty (15.6%) subjects experienced mild to moderate adverse events, mostly gastrointestinal. Conclusion: Postmenopausal women with osteoporosis prefer and are more satisfied and compliant with monthly dosing of ibandronate than daily or weekly bisphosphonate treatment. (Turkish Journal of Osteoporosis 2012;18:1-7)
Günlük veya haftalık alendronat veya risendronat alan postmenopozal osteoporozlu kadınlarda aylık ibandronat için hasta tercihinin değerlendirildiği açık- etiketli, prospektif, çok-merkezi, iki-aşamalı çalışma-BONCURE: Türkiye alt-çalışması
Keywords: Genel ve Dahili Tıp